The Effectiveness of Distraction Techniques for Pain in Fracture Patients in Sundari General Hospital, Medan - Youlanda Sari; Nurul Haflah; Isty Putri Utami; Abdullah Aziz (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
The impact of fracture is discontinuity and tissue damage. If not treated immediately will cause complications. There needs to be management that can prevent complications. Pain experienced by patients can be known by measuring using a pain scale.  If not treated immediately will cause complications. There needs to be management that can prevent complications. Surgical management includes closed reduction, fixation, open reduction, Open Reduction External Fixation (OREF), and Open Reduction Internal Fixation (ORIF). Distractions have the best effect for short periods of time, for example during invasive procedures or while waiting for analgesics to work. Distraction techniques can be applied to patients with acute pain, chronic pain and anxiety patients. The role of the nurse is to provide physical health services to the patient, namely as a care giver and to the patient's psychological health, namely as an educator. Nurses must be able to provide comfort so that patients avoid pain.  So, nurses should combine pharmacological and non-pharmacological management such as providing distraction techniques according to SOP to reduce pain. This research is a quantitative research with a quasi-experimental research type. With the treatment group by measuring the level of pain before the distraction technique was carried out with the control group by measuring the level of pain after the distraction technique was carried out. Statistical test results showed that there were differences in pain levels before and after the distraction technique was performed with a p value of 0,017 (0.15). Distraction technique is effective for reducing the pain level of post ORIF extremity fracture patients at Sundari General Hospital in Medan. Should be able to apply more distraction techniques as non-pharmacological therapy to reduce pain in accordance with established operational standards. Keywords : Distraction technique, Fracture, Pain